Iron Status in Pre-Eclampsia: A Case-Comparison Study (Bangladesh Journal of Medical Biochemistry, 2013)
Preeclampsia is one of the most leading causes of maternal mortality in developing countries. Many studies have demonstrated the relation between alteration of iron status and preeclampsia. The aim of the study was to assess the status of iron in preeclampsia. This case control study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total number of 100 pregnant women in the third trimester of pregnancy attending the Obstetrics & Gynaecology Department of Dhaka Medical College Hospital were selected purposively as study subjects. Among them 50 diagnosed cases of preeclampsia were selected as cases and 50 normal healthy pregnant women as controls. Serum ferritin and serum iron concentration were measured in all study subjects. The mean serum ferritin concentration in cases and controls were 95.06±50.07 ?g/l and 45.56±27.44 ?g/l respectively. Mean serum iron concentration in cases was 121.78±41.93 ?g/dl and that in controls was 61.04±24.18 ?g/dl. The present study showed significant differences of mean serum ferritin and serum iron between cases and controls. The study revealed presence of significantly higher level of serum ferritin and serum iron in preeclamptic group. DOI: http://dx.doi.org/10.3329/bjmb.v5i2.13345 Bangladesh J Med Biochem 2012; 5(2): 53-55